2008
DOI: 10.2133/dmpk.23.406
|View full text |Cite
|
Sign up to set email alerts
|

Influence of SLCO1B3 Gene Polymorphism on the Pharmacokinetics of Digoxin in Terminal Renal Failure

Abstract: Digoxin (DX) is mainly excreted unchanged in the urine. In patients undergoing hemodialysis (HD patients), the relative contribution of hepatic elimination is increased. DX is a substrate of OATP1B3 (SLCO1B3), expressed on the sinusoidal membranes of hepatocytes in humans. Therefore, we investigated the relationship between SLCO1B3 gene polymorphisms and the value of trough concentration-to-dose ratio (C/D ratio) of DX in HD patients. We investigated two deletion polymorphisms in complete linkage disequilibriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 19 publications
1
18
1
Order By: Relevance
“…Our data indicate that digoxin should not be used as a probe substrate for OATP1B3 in human hepatocyte systems. A previous clinical study suggested that an insert-variant allele of OATP1B3 was associated with an increase in the concentration/dose ratio of digoxin in patients on hemodialysis measured 62 to 72 h postdose (Tsujimoto et al, 2008). Although this finding appears to support a role for OATP1B3-mediated hepatic clearance in patients on hemodialysis, additional studies comparing this allele with the measured digoxin systemic clearance are needed to confirm these findings.…”
Section: Discussionmentioning
confidence: 91%
“…Our data indicate that digoxin should not be used as a probe substrate for OATP1B3 in human hepatocyte systems. A previous clinical study suggested that an insert-variant allele of OATP1B3 was associated with an increase in the concentration/dose ratio of digoxin in patients on hemodialysis measured 62 to 72 h postdose (Tsujimoto et al, 2008). Although this finding appears to support a role for OATP1B3-mediated hepatic clearance in patients on hemodialysis, additional studies comparing this allele with the measured digoxin systemic clearance are needed to confirm these findings.…”
Section: Discussionmentioning
confidence: 91%
“…For example, metformin, digoxin, rosuvastatin, and sitagliptin are not (extensively) metabolized, but drug transporters have key roles in the disposition or efficacy of these compounds (see drugs labels at http://www.accessdata.fda.gov/ scripts/cder/drugsatfda/index.cfm). Metformin is a substrate for OCT1 and 2 [33,34], rosuvastatin is a substrate for OATP1B1 [35], digoxin is a Pgp substrate [36] and sitagliptin a substrate for OAT3 [37]. As remogliflozin etabonate and its metabolites are not strong inhibitors of transporters, there are expected to be no drug interactions between remogliflozin etabonate and these agents.…”
Section: Discussionmentioning
confidence: 99%
“…SLCO1B3 genotype analysis of Ins/Del, 334T>G and 699G>A polymorphisms was performed using respectively 3 primers for exon 1, 3, and exon 6 as previously described [20]. Cycling conditions were an initial denaturation stage carried out at 94°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, 2 deletion polymorphisms from position (-28 to -11) and from position (-7 to -4) in exon 1 were apparently associated with the reduction of concentration-to-dose ratio of digoxin in terminal renal failure. Additionally, some studies have shown that SLCO1B3 334T>G (Ser112Ala; rs4149117) and 699G>A (Met233Ile; rs7311358) modulate the transport activity and may influence drugs pharmacokinetics including digoxin [19,20]. Nevertheless, Smith et al [21] (2007) have shown no association of drug pharmacokinetics with these genetic polymorphisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation